The Controlled Arena of Contested Practices: Critical Practice in Israel's State Social Services. (16th July 2020) - Timor-Shlevin, Shachar
Abstract: Scholars claim that the integration of critical social work into public social services is impossible considering its weak position in the managerialist context of these services. Consequently, critical practice is mainly described as covert and reflective of the hierarchical power dynamics between managerialism and critical professionalism. Thus, the option of integrating critical social work into the institutionalised operation of the profession, which involves engaging in critical practice to the extent possible in the context of public services beyond micro and covert practices, has not been sufficiently described. This study addresses this gap, exploring the process of implementing the critical professional 'Poverty-Aware Social Work Paradigm' (PAP) into the Israeli public welfare services. Based on twenty-five interviews with field-level social workers in the PAP programmes, the findings describe critical practices as operating simultaneously at the interpersonal and structural levels, mainly through covert actions. The discussion illustrates the significance of merging the interpersonal and structural levels of critical practice and describes the limited arena in which critical professionalism operates in public services.